Pendampingan Pembuatan Label Kemasan pada Produk UMKM Rengginang Putra Kembar Desa Pasirnagara Kecamatan Pamarican Kabupaten Ciamis - Muchtar, Ayi Ishak Sholih; Fitria, Ai Wina; Aziz, Daffa Abdul (Lembaga Pengabdian kepada Masyarakat (LPkM) Universitas Islam Darussalam (UID) | Islamic University of Darussalam Ciamis-Jawa Barat, 2022)
This study summarizes community service efforts aimed at increasing competitiveness , improving the quality and attractiveness of packaging labels which in turn can have a positive impact on the marketing of Rengginang Putra Kembar Micro, Small and Medium Enterprises (MSMEs) products in Pasirnagara Village. The type of research used is a qualitative method . The data collection techniques used in this research are interviews and observation. The main focus of this program is making product packaging labels as an integral part of the brand image and marketing strategy of MSMEs. Packaging label assistance for MSMEs is a process where competent or expert parties provide guidance, training, or advice to MSMEs in designing, producing, or improving their product packaging labels. The results of this research show that assistance in making packaging labels for Rengginang Putra Kembar MSME products has provided real benefits for these MSMEs.